Improved physics-based analysis to discriminate the flicker noise origin at very low temperature and drain voltage polarization. (September 2020) - Cretu, B.; Boudier, D.; Simoen, E.; Veloso, A.; Collaert, N.; Claeys, C.
Highlights: Low frequency noise study is performed at deep cryogenic temperature of 10 K in p-channel gate-all-around (GAA) nanowire (NW) FETs. The results show that for the lower drain biases considered in this work, the flicker noise behavior may be explained using physical-based models derived from classical transport considerations for cryogenic temperatures by the mobility fluctuations mechanism originating from Coulomb scattering interactions. This may be surprising, and suggests that even if step-like effects impact the DC measurements, there is a polarization interval in which they do not impact the 1/f noise. This suggests that the responsible transport mechanism for 1/f noise and for the step-like current behavior observed may have different origins. Abstract: Low frequency noise study is performed at deep cryogenic temperature of 10 K in p-channel gate-all-around (GAA) nanowire (NW) FETs. As expected, the carrier number fluctuations mechanism explains the flicker noise origin for conventional fixed applied drain bias. At very low applied drain biases step-like effects impact the drain current transfer characteristics. Noise measurements performed at a fixed very low drain voltage as a function of the applied gate bias show that the gate voltage flicker noise behavior follows a I DS 3 / 2 / g m 2 law. It was already proved that this dependency may be modeled considering classical transport theory, in the framework of the mobility fluctuations mechanism from Coulomb scattering interactions. The noise measurements performed at fixed gate voltage as a function of the applied drain bias show that the gate voltage 1/ f noise levels present a deviation from the I DS 3 / 2 / g m 2 law. In order to explain this behavior, an improved model is proposed mainly considering some additional hypotheses: the inversion charge dependency on the applied drain bias and the fact that the impact of the drift component of the drain current may be neglected when measurements are made at low fixed gate voltage biases for very low applied drain voltages. The results show that for the lower drain biases considered in this work, the flicker noise behavior may be explained using physical-based models derived from classical transport considerations for cryogenic temperatures by the mobility fluctuations mechanism originating from Coulomb scattering interactions. This may be surprising, and suggests that even if step-like effects impact the DC measurements, there is a polarization interval in which they do not impact the 1/ f noise.